2022
DOI: 10.1177/1357633x211069663
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of telehealth programs on the mental health of women with breast cancer: A systematic review

Abstract: Objective The purpose of this systematic review is to determine the evidence-based information and results about the effectiveness of telehealth programs on the mental health of women with breast cancer. Methods: The research process was carried out using PRISMA guidelines. Randomized controlled trials with available abstract and full text, which were published in English with the keywords “telehealth,” “telemedicine,” “web-based therapy,” “telepsychiatry,” "online therapy" and "breast cancer" in Pub Med, Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Examples include telehealth programs which aim to improve mental health in women with BC. [41] In regard to this study's internal validity, one of the main limitations of this work is the classi cation of mental health illnesses. CCI software was used to group mental health diagnoses because the sources of information come from different autonomous communities in Spain.…”
Section: Discussionmentioning
confidence: 95%
“…Examples include telehealth programs which aim to improve mental health in women with BC. [41] In regard to this study's internal validity, one of the main limitations of this work is the classi cation of mental health illnesses. CCI software was used to group mental health diagnoses because the sources of information come from different autonomous communities in Spain.…”
Section: Discussionmentioning
confidence: 95%
“…They recommended psychoeducation, psychotherapy, or physical activities (walking, mind–body practice, etc.). These studies were not included in the present analysis, as no CGA was performed, and interventions were not specifically designed for patients over 65 years old [ 18 , 19 ]. Cognition has a high impact on the feasibility of a care plan, and its assessment is crucial in the decision-making process.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, other studies have reported that it reduces depressive symptoms (45). Research ndings in a similar study conducted with women diagnosed with breast cancer and receiving active treatment show that depression levels are directly related to individuals' coping styles, and depression levels decrease as individuals' coping styles become functional (46).…”
Section: Discussionmentioning
confidence: 99%